-12x-16=89

Simple and best practice solution for -12x-16=89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12x-16=89 equation:


-12x-16=89

We simplify the equation to the form, which is simple to understand
-12x-16=89

We move all terms containing x to the left and all other terms to the right.
-12x=+89+16

We simplify left and right side of the equation.
-12x=+105

We divide both sides of the equation by -12 to get x.
x=-8.75

See similar equations:

| 2n/4n^1/2 | | (X-3)(X+6)= | | 2/3x-1/2x=-1/6x-2 | | 4x-6+x+6y=180 | | 3.2(0.5x+.8)=x-.7(3x-.25) | | 4X-(48/x^2) | | 3/7x=6y-3 | | -7x+15/6y=-x+1 | | 12m=4(5m+10) | | 11x+19y=29fory | | (5/8)(4/3) | | (6/5)/(6/7) | | (7/20)-(3/25) | | -8x^3-x^2-64x^2-8x+24x+3= | | (3/6)+(2/7) | | 4x^2+3x-23=5-6x | | (8)x/8=x | | (x/(x+1))-(4/(x-2))=2 | | -0.3x+1.13=-0.1x+0.73 | | R+.07=142 | | 110/240 | | (7-2i)(4-3i)= | | (5v-2)(6v+v)=0 | | 7(x-3)+x(x+4)=5 | | -5b+3(b+2)+4(b+1)=2 | | 60-x=54 | | -[-3(3x-5y)-1]= | | 3a-[3a-3(a)]= | | 12p-6(3p+4)-(4-p)= | | 6.25*-2.72+17= | | x^2+-6x+25=0 | | 9x^2-16x+60=0 |

Equations solver categories